Androgenic steroid composition of the hexane/ methanol whole plant extract of Solanecio tuberosus (Selbilla) around Lake Tana Northwest Ethiopia - Menyechil Yenealem Antigegn, Seleshi Andualem Mekuriaw, Endalkachew Nibret Semegn, Zewdie Mekonnen Nigussie (Journal of Medicinal Herbs and Ethnomedicine, 2015)
The plant kingdom is a treasure house of potential drugs. Steroids are very important molecules that mediate a wide range of biological functions in the human body. Today, there is no study reporting the androgenic steroid content of Solanecio tuberosus extract. In this study, the androgenic steroid content of hexane/methanol extract of S. tuberosus was analyzed by Fourier transform (FT)-infrared spectroscopy, ultraviolet-visible spectroscopy, FT-magnetic resonance spectroscopy, and thin layer chromatography. Androgenic steroid derivatives such as predinsolone, testosterone cypionate, and methyltestostrone were identified. The present study showed that S. tuberosus can be considered as a potential remedy to improve the sexual and physical health of men as they go aged and in testosterone deficient condition if further studies are conducted on safety and efficacy of the plant material.